6(x-3)-7x+7=-11

Simple and best practice solution for 6(x-3)-7x+7=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)-7x+7=-11 equation:



6(x-3)-7x+7=-11
We move all terms to the left:
6(x-3)-7x+7-(-11)=0
We add all the numbers together, and all the variables
-7x+6(x-3)+18=0
We multiply parentheses
-7x+6x-18+18=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0

See similar equations:

| 6(1-x)=16-4x | | 39-12w=7-17w | | -6k-8=-9k+10 | | 2r-2=-r+10 | | 28x-5=79 | | 8x+4(x+1)=15x-10 | | 275=t-118 | | 3÷w+6=8 | | (2w-8)(6w+1)=0 | | |-2n|=-50 | | |4n-4|+8=12 | | 88(2f-3)=4(4f-8) | | 4(m+3)=m-15 | | 3u+46=1+8u | | 3(u-13)+6=18 | | x+6=13x=8 | | 2(3x+7)-8=0 | | 12=-3x+-21 | | 9-5x=5x-8 | | -3+v/7=-1 | | p+7=803 | | 109-w=227 | | (3)=2x^2+5x-7 | | -6x+3=2x-4 | | 3x+x+2x+1=19 | | -5x-{-7-4x}=-2{3x-4} | | 2(3x+7-8=0 | | 12t=20+7t | | -3(r+6)=44 | | x+-6=x+6 | | 12f=420 | | 9(x+4)=4 |

Equations solver categories